The Invisible Victims of Imprisonment: An Integrative Review of the Social and Emotional Challenges of Children with Incarcerated Parents - Adebayo Lydia (Universitas Medan Area, 2026)
Children with incarcerated parents remain statistically and institutionally overlooked despite growing evidence of emotional, relational, educational, and material harm. Existing studies often isolate single outcomes, privilege adult reports, or concentrate on high income Western settings, leaving limited synthesis of how relational and structural mechanisms interact, particularly in African contexts. This integrative review synthesised 27 publications, from 2022 to 2026, using explicit eligibility criteria, critical appraisal, and thematic coding informed by attachment theory and the family stress proximal process model. Findings shows that parental incarceration may generate ambiguous and disenfranchised loss, anxiety, depression, behavioural dysregulation, and physiological stress; however, outcomes vary according to prior adversity, the preincarceration relationship, caregiver continuity, and the circumstances of arrest and imprisonment. Stigma, poverty, school disruption, unstable care, and unequal access to services frequently intensify emotional distress. Secure caregiving, developmentally appropriate truth, supportive schools, and emotionally safe contact can be protective, but intervention evidence remains limited and uneven in quality. The review’s theoretical contribution is an integrated pathway in which incarceration related shocks affect children through material strain and proximal family processes, with institutional support and children’s agency shaping outcomes. Practically, the findings support child impact assessments, routine identification of dependent children, caregiver assistance, confidential school protocols, and child centred contact policies. The review concludes that parental punishment should not become unexamined punishment of the child, while cautioning against treating all affected children as uniformly damaged or passive.